Thermomechanical fatigue failure investigation on a single crystal nickel superalloy turbine blade. (August 2016) - Wang, Rongqiao; Jiang, Kanghe; Jing, Fulei; Hu, Dianyin
Abstract: A thermomechanical fatigue (TMF) test rig was developed consisting of the loading, heating, synchronizing, cooling and monitoring systems. Moreover, the specimen was particularly designed to provide adequate load-bearing capability at the blade tip in order to simulate the actual turbine blade loads in laboratory. TMF test on a single crystal nickel superalloy turbine blade was conducted. Then the specimen was segmented in a novel way to preserve the crack surface to investigate the TMF mechanism of the turbine blade. Visual examination together with the metallographic analysis indicated that the most severe TMF damage occurred at the pin-fin fillet on the suction side near the trailing edge. Furthermore, finite element simulation results were compared to the experiment, in which a viscoplastic constitutive model was employed. Highlights: A thermomechanical fatigue test rig for the actual turbine blade was constructed. The specimen was designed to guarantee adequate load-bearing in the connection. SEM samples with well-preserved crack surfaces were prepared in a novel way. The severest damage appeared at the pin-fin fillet, consistent with the FE simulation.